An assessment of CSR disclosures in Polish listed companies - Węgrzyńska, Małgorzata (Publishing House of Wroclaw University of Economics and Business, 2024)
Identifying, measuring and evaluating reporting information provided by economic entities is a challenge for its recipients. So far, scientific research has only dealt with evaluating information contained in financial statements, namely financial data. However, economic entities report non-financial information in addition to financial information. Global studies attempt to measure non-financial information, using disclosure indices. The objective of this article was to determine the relations of the information provided in the reports of the studied companies regarding corporate social responsibility (CSR) with selected financial results and to determine the degree of linguistic difficulty with statistical analysis of the studied text. The study was conducted on a selected group of 70 companies listed on the Warsaw Stock Exchange in Poland between 2013 and 2018. In total, 420 financial statements and 420 CSR reports were studied. The research employed three readability indices: the FGL index, the FOG index (three variants) and Pisarek’s index (six variants) and a statistical analysis of the text was performed. In the next study phase, a panel regression model was used to examine the relationship between non-financial information and financial information. The main conclusion that emerged from the study was that there are differences between disclosure indices and the scale of disclosure in Polish listed companies. Furthermore, in some cases, non-financial information showed a relation with financial information.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 240-261
Keywords: CSR; readability indices; FOG index; FGL index; Pisarek’s index